Development of Smart Wheel Chair with Dual Control: Smart Phone and Hand Gesture - Priya Darshini B, Aswini Ramamoorthy, Yamuna V.K, Lingatharani N (Mathematical Statistician and Engineering Applications, 2023)
Physically challenged individuals with severe motor impairment face difficulty with the existing wheelchair as they cannot process command by means of conventional joystick. By, designing a semi-automatic wireless smart wheelchair which can adapt to be used indoor and outdoor those hassles can be eliminated. This also aids the user by minimizing the physical and cognitive load required in steering an electric wheelchair. MEMS sensor, an accelerometer sensor with three-axis measures the orientation of hand from the user and interprets the hand motion. Bluetooth module integrated with an android application recognizes the commands through various buttons in the smart phone pressed by the user, which has different set of values programmed for different direction including an emergency stop button. Arduino UNO is the microcontroller used to control the whole process of the system. The proposed system is efficient to reduce the effort taken by the individual to propel it manually. The future developments as GPS based voice navigation system, speed control system and safety belts make it highly advanced mobility solution for disabled individuals. These features in the prototype also makes it viable and safe to the user and environment.